Estimating the Strategic Value of Long‐Term Forward Purchase Contracts Using Auction Models - PARSONS, JOHN E. (Journal of Finance, 1989)
ABSTRACT We demonstrate how an auction model can be used in a traditional capital budgeting context to assign a value to the strategic advantage of long‐term forward contracts. Research in the field of industrial organization has pointed to the danger of ex post opportunistic bargaining as a motivation for the use of forward contracts in natural resources and manufactured products, but no operational procedure exists for estimating the value secured by these contracts. Arbitrage methods for valuing forward contracts assume a competitive market in which the factors creating the bargaining problem and motivating the use of long‐term contracts are not present. Use of the model is illustrated in the case of take‐or‐pay contracts for natural gas.